2019
DOI: 10.1002/elan.201800834
|View full text |Cite
|
Sign up to set email alerts
|

3D‐printed Portable Platform for Mechanized Handling and Injection of Microvolumes Coupled to Electrochemical Detection

Abstract: We present a low‐cost mechanized system fabricated using fused deposition modelling 3D‐printing technology to manipulate microvolumes and perform injections on an electrochemical cell in wall‐jet configuration. As a proof‐of‐concept, the amperometric detection of paracetamol (model analyte) on a screen‐printed electrode using 0.5 μL aliquots resulted in highly reproducible responses (RSD <3 %). Moreover, handling of microliter aliquots of butylhydroxytoluene (phenolic antioxidant) and 2,2‐diphenyl‐2‐picrylhydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…7 As this technology is continually advancing, it has opened new horizons in other research domains, such as analytical chemistry 8,9 and electrochemistry. 10,11 Examples of AM/3D printed electrochemical sensors and devices found in literature include; sensing electrodes, 10 electrochemical cells, 2 microuidic devices, 12 microneedles, 13 supercapacitors 14 and reaction ware for chemical synthesis and analysis. 15 The fabrication of ow cells for analytical purposes has been presented by commercial companies, such as Metrohm, 16 Antec Scientic, 17 BASI® 18 and ERC Co. 19 There have also been reports in the scientic literature of fabricating ow cells for further applications in ow-injection analysis, 20,21 electrochemiluminescent analysis, 22 studying biological redox reactions, 23 mechanistic and kinetic studies, 24 electrochemical degradation of dye 25 and environmental sciences.…”
Section: Introductionmentioning
confidence: 99%
“…7 As this technology is continually advancing, it has opened new horizons in other research domains, such as analytical chemistry 8,9 and electrochemistry. 10,11 Examples of AM/3D printed electrochemical sensors and devices found in literature include; sensing electrodes, 10 electrochemical cells, 2 microuidic devices, 12 microneedles, 13 supercapacitors 14 and reaction ware for chemical synthesis and analysis. 15 The fabrication of ow cells for analytical purposes has been presented by commercial companies, such as Metrohm, 16 Antec Scientic, 17 BASI® 18 and ERC Co. 19 There have also been reports in the scientic literature of fabricating ow cells for further applications in ow-injection analysis, 20,21 electrochemiluminescent analysis, 22 studying biological redox reactions, 23 mechanistic and kinetic studies, 24 electrochemical degradation of dye 25 and environmental sciences.…”
Section: Introductionmentioning
confidence: 99%
“…The resolution is much higher than the FFF 3D-printed devices, however, longer time of fabrication, the need for post-treatment and curation, and the use of toxic resins are some drawbacks that make SLA less popular than FFF. Nevertheless, one of the first works on the Bismuth film electrodeposition 3D-printed wearable device containing the electrochemical device was fixed at the body using an elastic tape for zinc determination in sweat Dias et al (2019) Images reproduced with permission from American Chemical Society (Snowden et al, 2010;Richter et al, 2019;Sempionatto et al, 2017;Katseli et al, 2021;Dias et al, 2019), Italian Association of Chemical Engineering (Ponce de Leon et al, 2014), Elsevier (Dias et al, 2016;Cardoso et al, 2018;Mendonça et al, 2019;Cardoso et al, 2019;Silva et al, 2020;Escobar et al, 2020;Sibug-Torres et al, 2021;Cardoso et al, 2020c;Ferreira et al, 2021;O'Neil et al, 2019;Baltima et al, 2021); Brazilian Chemical Society (Cardoso et al, 2020a), Royal Society of Chemistry (Elbardisy et al, 2020) and Multidisciplinary Digital Publishing Institute (Vlachou et al, 2020).…”
Section: Examples Of 3d Printer Applications In Electrochemical Devices 3d Printed Electrochemical Cells For Sensing and Other Applicatiomentioning
confidence: 99%
“…Hence, these 3D-printed electrochemical cells require other parts that were not 3Dprinted. The same research group reported a portable, mechanized, and fully 3D-printed platform that comprises an autosampler, injection syringe pump, and electrochemical cell (Mendonça et al, 2019). This platform (43 × 28 × 15 cm) can manipulate microvolumes (0.5 µl) from a sample tray containing 68 vials and inject over a screen-printed electrode placed inside a 3D-printed electrochemical cell (inner volume from 50 to 10 ml) using a 3D-printed syringe pump.…”
Section: Examples Of 3d Printer Applications In Electrochemical Devices 3d Printed Electrochemical Cells For Sensing and Other Applicatiomentioning
confidence: 99%
“…The attractive features of the BIASPE system were also explored for the on-site determination of carbendazim, catechol and hydroquinone in tap water, [20] metals (Zn 2 + , Cd 2 + , Pb 2 + , Cu 2 + , and Hg 2 + ) in biodiesel samples, [85] glucose in artificial serum sample, [21] antioxidant 2,6-di-tert-butylphenol (2, in biodiesel and jet-fuel using hydro-organic media as the supporting electrolyte, [26] lead in aviation fuel samples, [86] omeprazole in pharmaceutical samples, [87] corrosion inhibitors (2,5-dimercapto-1,3,5-thiadiazole) in fuel ethanol, seawater and mineral oil samples, [88] levamisole and sodium levothyroxine in pharmaceutical samples, [89] nitrite and uric acid in biological fluids (urine, plasma, saliva, and serum), [90] antioxidant capacity of edible oil samples, [91] benzocaine and tricaine in fish fillets, [92] and a robust electroanalytical system for detection of UVinduced DNA degradation. [93] Recently, Mendonça et al [94] reported a low-cost mechanized system fabricated using fused deposition modelling 3D-printing technology to perform injections on an electrochemical cell in wall-jet configuration (similar to a common BIA cell). Expanding the possibility for analysis with extremely small volumes (0.5 μL), the system also allows automatic handling of microliter aliquots (dilutions, mixtures, exactly time-controlled reactions), similar to FIA and SIA systems.…”
Section: -Nitro-p-phenylenediaminementioning
confidence: 99%